Methicillin resistant Staphylococcus aureus causing osteomyelitis in a tertiary hospital, Mwanza, Tanzania - Vitus Silago; Martha F. Mushi; Boniface A. Remi; Alute Mwayi; Stephen Swetala; Conjester I. Mtemisika; Stephen E. Mshana (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background Culture results of fluid/pus from sinuses or open wound are not reliable in establishing the causative agent of osteomyelitis due to the high chances of contamination of superficial contaminants. Bone fragments obtained during surgery have been recommended as ideal sample to establish pathogens causing osteomyelitis. This study investigated pathogens causing osteomyelitis among patients undergoing orthopedic surgical treatment at Bugando Medical Centre. Methods A cross-sectional hospital-based study was conducted from December 2017 to July 2018 among 74 patients with osteomyelitis who underwent surgical treatments at Bugando Medical Centre, Mwanza, Tanzania. Bone fragments were collected using sterile 10 ml of in-house prepared brain heart infusion broth (Oxoid, UK) during surgery. Specimens were processed according to standard operating procedures within an hour of collection. Data were analyzed using STATA 13.0. Results The median age of study participants was 12 with inter quartile range of 8–20 years. The majority 45 (60.8%) of participants were male. All 74 non-repetitive bone fragment specimens had positive culture, of which 17 had dual growth of bacteria resulting to 91 bacterial isolates. Out of 91 isolates, 63 (85.1%) were Staphylococcus aureus (S. aureus) of which 18 (28.6%) were confirmed to be methicillin resistant Staphylococcus aureus strains. Fever was significantly associated with Staphylococcal osteomyelitis (100% vs. 79.6%, p = 0.029). Conclusion About one third of cases of Staphylococcal osteomyelitis in the current study were caused by methicillin resistant Staphylococcus aureus. There is a need of tailoring antibiotic management of osteomyelitis based on culture and sensitivity results for the better treatment outcome of the patients.